Analyzing the Impact of Programming Mistakes on Students' Programming Abilities - dos S. Júnior, Antonio D.; Figueiredo, Jorge; Serey, Dalton (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
Despite all the research on students' misconceptions in introductory programming courses, there is still a lot to understand about how they make and correct mistakes. The reviewed works investigate code as a final, static artifact, but this does not tell the whole story about the students' mistakes. With this study, we take the first step toward an attempt to close this gap. By capturing granular states of the coding process, we collected and analyzed data in an experiment with twenty-two novice students aged 14 to 16. With the experiment, we found the most common issues in the students' code. This enabled us to know which mistakes may prevent them from reaching a correct solution, and which will not interfere but may show an understanding problem in core programming concepts. This experiment precedes the development of an approach to help the teacher or teaching assistant in providing personalized and directed help to the students in programming courses.